Tax Appeal - An Instrument for Defending the Taxpayers' Rights - Ciobanu, Ramona (Transilvania University Press, 2014)
The legislative consecration of the taxpayer's right to appeal tax administrative acts represents a guarantee of the rule of law. The Romanian legislator provides the taxpayer with two important defense tools to protect his/her rights in fiscal procedures: the fiscal appeal and the administrative and fiscal action. The Fiscal Procedure Code and the Administrative Court Proceedings Law no.554 / 2004 govern the terms, conditions, procedure, and the fiscal authorities or the competent courts. These legal provisions are intended to protect taxpayers from the possible illegal actions and abuses of tax authorities.
Keywords: tax administrative act; tax appeal; taxpayers